EFFECTS OF THE OTAGO HOME EXERCISE PROGRAM ON FALL RISK AMONG OLDER ADULTS - Vita Lucya; Popi Bunga Ropikoh (Jurnal Keperawatan PPNI Jawa Barat, 2025)
Background: Aging is accompanied by progressive physiological changes that reduce physical function, balance, and mobility, thereby increasing the risk of falls among older adults. Falls are a major cause of morbidity, functional decline, and reduced quality of life in the elderly population. Effective and feasible fall-prevention interventions are therefore essential. The Otago Home Exercise Program (OHEP) is a structured strength and balance training program designed to reduce fall risk in older adults. Objective: This study aimed to examine the effect of the Otago Home Exercise Program on fall risk among older adults. Methods: A quasi-experimental study with a two-group pretest–posttest design was conducted involving 60 participants aged 60 years and older, selected using purposive sampling. The intervention group received the OHEP three times per week for three weeks, while the control group received usual care. Fall risk was assessed using the Timed Up and Go Test (TUGT). Data were analyzed using the Wilcoxon signed-rank test and the Mann–Whitney U test. Results: A significant reduction in fall risk was observed in the intervention group following the program (p = 0.000). High fall risk decreased from 10% to 0%, moderate risk decreased from 90% to 80%, and low fall risk increased from 0% to 20%. Conclusion: The Otago Home Exercise Program is effective in reducing fall risk among older adults and is recommended for implementation in elderly care and community health settings